THE EFFECT OF PROFITABILITY, COMPANY SIZE, AND MANAGERIAL OWNERSHIP ON DEBT POLICY - Septiani, Meli; Daryanti, Sri (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study is to examine the impact of profitability, firm size, and managerial ownership on debt policy in manufacturing companies listed on the Indonesia Stock Exchange between 2018 and 2020. This study used 50 companies from 166 manufacturing companies that had been selected according to sample criteria using the purposive sampling method. Eviews version 12.0 was used to process the data, and the statistical method utilized was multiple linear regression. In this study, partial test results show that profitability and ownership of management do not have a significant impact on debt policy, while the variables of firm size have positive and significant impact on firm debt policy. However, in this study, simultaneous test results show that variables of profitability, firm size, and ownership of management variable have a significant impact on firm debt policy.